2014
DOI: 10.1007/s10162-014-0457-9
|View full text |Cite
|
Sign up to set email alerts
|

Modulation Enhancement in the Electrical Signal Improves Perception of Interaural Time Differences with Bimodal Stimulation

Abstract: Interaural timing cues are important for sound source localization and for binaural unmasking of speech that is spatially separated from interfering sounds. Users of a cochlear implant (CI) with residual hearing in the non-implanted ear (bimodal listeners) can only make very limited use of interaural timing cues with their clinical devices. Previous studies showed that bimodal listeners can be sensitive to interaural time differences (ITDs) for simple single-and three-channel stimuli. The modulation enhancemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 43 publications
3
22
0
Order By: Relevance
“…In particular Francart et al (2009) and Francart et al (2011) used the 50%-correct point from a constant stimuli procedure, which may lead to lower JNDs than estimated with the typically used target point of the adaptive procedure of around 70%. However, Francart et al (2014) compared the results of their constant stimuli procedure with an 1up/2down, 70% correct, -ITD +ITD procedure, and found similar results when the thresholds obtained from the adaptive procedure were multiplied by 2.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…In particular Francart et al (2009) and Francart et al (2011) used the 50%-correct point from a constant stimuli procedure, which may lead to lower JNDs than estimated with the typically used target point of the adaptive procedure of around 70%. However, Francart et al (2014) compared the results of their constant stimuli procedure with an 1up/2down, 70% correct, -ITD +ITD procedure, and found similar results when the thresholds obtained from the adaptive procedure were multiplied by 2.…”
Section: Resultsmentioning
confidence: 87%
“…With current fitting and sound coding strategies, it is unlikely that CI users with contralateral normal-hearing (or impaired hearing) would be able to use ITD cues in practice because (1) the required temporal information is poorly coded by most CI sound processing strategies (Francart et al, 2014), (2) many CI sound processors have a processing delay longer than the required delay of electrical stimulation for synchronisation with the acoustic signal, and for broad-band signals the delay of the sound processor does not vary in the same way with frequency as the delay of the traveling wave in the acoustically stimulated ear, (3) with the standard frequency-to-electrode allocation of the sound processor, the place of stimulation in the two cochleae is not optimally matched for ITD perception, for most subjects (4) for the human head size, the maximal physically plausible ITD is around 690 us (Feddersen, 1957). If the smallest ITD that can be detected is in the best case 200 μs, and in many cases much more, it is unlikely to yield much practical use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In practice, this could be achieved in a sound processor by using either a single modulation waveform to modulate all channel envelopes, such as in the Modulation Enhancement Strategy (Francart et al 2014), or using overlapping filters in the filter bank from which the envelopes are extracted, which may be optimized as a good compromise between providing sufficiently comodulated signals and providing separate information channels. Delays in this order of magnitude were tested in the present study.…”
Section: Consequences For Sound Processorsmentioning
confidence: 99%
“…Despite the significant degree of acoustic ear hearing loss, it may be possible that even limited overlapping frequency regions could support binaural computation of ITDs and ILDs, which may improve sound localization performance (Francart et al, 2009b;Veugen et al, 2016b). Sensitivity to ITDs has been demonstrated in bimodal listeners in laboratory conditions using highly controlled stimuli (e.g., pulse trains or noise stimuli with experimental devices under direct computer control of electrode stimulation patterns; Francart and Wouters, 2007;Francart et al, 2009b;2011b;Francart et al, 2014). However, another study found that even for individuals trained on an ITD task (n 5 3), they demonstrated no or little sensitivity to transposed sinusoids or pulse trains (Lenssen et al, 2011).…”
Section: Bimodal Auditory Cue Preservationmentioning
confidence: 99%